Evolution of self‐perceived swallowing function, tongue strength and swallow‐related quality of life during radiotherapy in head and neck cancer patients. Issue 7 (14th February 2019) - Van den Steen, Leen; Van Gestel, Dirk; Vanderveken, Olivier; Vanderwegen, Jan; Lazarus, Cathy; Daisne, Jean‐François; Van Laer, Carl; Specenier, Pol; Van Rompaey, Diane; Mariën, Steven; Lawson, Georges; Chantrain, Gilbert; et al.
Abstract: Background: Radiation‐associated‐dysphagia is a serious side effect of radiotherapy (RT) for head and neck cancer (HNC). Methods: Seventy‐six patients had a weekly prospective follow‐up from baseline until one week post‐RT. Combined mixed model analysis ( n = 43) determined the evolution of self‐perceived swallowing function, isometric tongue strength (MIP), tongue strength (TS) during swallowing (Pswal), and quality of life (QoL) in these patients during RT. Results: Swallowing deteriorated from the third week on, resulting in an increase of tube dependency from 10% at baseline toward 31% post‐RT. Both MIP and Pswal are reduced, with anterior MIP decreasing in 29% of patients and posterior MIP in 17%. Pswal decreases for saliva and a bolus swallow. All QoL subscales except "sleep" were affected during RT. Conclusions: Self‐perceived s wallowing function, TS and QoL decrease during RT for HNC. Current findings highlight the need for early monitoring of these parameters.